PENGARUH MODEL INQUIRY-BASED LEARNING (IBL) TERHADAP PENINGKATAN PENALARAN KRITIS SISWA DI SEKOLAH MI MA'ARIF AT-TAQWA KALANGANYAR KARANGGENENG LAMONGAN - Lutfatin Nihayah; Ida Latifatul Umroh; Saefrudin (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
This research is motivated by the low critical reasoning ability of fourth-grade students at MI Ma'arif At-Taqwa Kalanganyar due to learning that is still conventional and teacher-centered. The objectives of this study are: (1) to analyze the effect of the Inquiry-Based Learning (IBL) model on improving students' critical reasoning, and (2) to determine the magnitude of its effect in the subject of Pancasila Education. This study employed a quantitative approach with a One Group Pretest-Posttest design involving 31 students (total sampling). The instrument used was a valid and reliable critical reasoning test. Data analysis utilized descriptive and inferential statistics (Shapiro-Wilk normality test, paired sample t-test, N-Gain, and Cohen's d effect size). The results of the study show: (1) the IBL model has a significant effect on improving students' critical reasoning with t-count = -13.643 and Sig. (2-tailed) = 0.000 (p < 0.05); (2) the effect size is large (Cohen's d = 1.397), while the improvement is in the moderate category (N-Gain = 0.40). These findings support Piaget's constructivism theory and Ennis's critical reasoning theory, and provide practical implications for teachers in using the IBL model as an effective strategy to develop students' higher-order thinking skills in Madrasah Ibtidaiyah.